Green Manufacturing and Sustainable Performance of Firms in North-Central Nigeria - Achem, Samson; Sule, Ja’afaru Garba; Ogbadu, Elijah (Acta Universitatis Danubius. Œconomica, 2025)
This study focused on green manufacturing and sustainable performance of firms in North-Central Nigeria. The study examined the extent to which green design affects environmental performance and determined the effect of green efficient processes on product quality. The study utilized a survey research design. A sample size 341 was established. A multi-stage sampling technique was utilized to ensure thorough representation. The study utilized construct validity and applied factor analysis. The study utilized both descriptive and inferential statistics for analyzing the data. Regression analyses were employed to test the established hypotheses. Findings showed that green design has a significant positive effect on environmental performance, and that green efficient processes have a significant positive effect on product quality. The study affirmed that green manufacturing significantly enhances the sustainable performance of firms. The study recommended that manufacturing firms should prioritize the integration of green design into their product development processes to enhance environmental performance, and that manufacturing firms should integrate green efficient processes into their operations to enhance product quality and competitiveness.